De l’usage des traces en sciences de l’information et de la communication - Béatrice Galinon-Mélénec; Julien Péquignot (Communiquer)
Following her doctoral thesis at the Sorbonne on the application of Pierre Bourdieu’s thought to Educational Sciences, and her involvement in establishing the communication of organizations as a research orientation in the Communication Sciences in France, Béatrice Galinon-Mélénec anchored her research in Communication Anthropology. This shift led her to found the Homme-trace (Human-Trace) paradigm. In this discussion, Béatrice Galinon-Mélénec looks back on her career path and explains how it lead her to an anthroposémiotique de la trace (human communication of the trace) based on an anthropological and co-constructivist perspective, a proposal offering a reading of signs seen as consequences of interactions between the “body-trace” and the “reality-trace”. It also clarifies its definition of the trace as a consequence, as well as one of indication, brand and footprint in relation to the trace. Finally, the researcher explains her vision of the research and investigation methods capable of capturing the complexity of reality through the “trace-consequences” that are variously accessible to humans.